The Impact of Marketing Mix of 4Ps (Product, Price, Place, and Promotion) towards Repurchase Intention with Customer Satisfaction as the mediator: In the Case of Uniqlo - Allwin Filbert; Wilson Anthony (iBuss Management, 2018)
The behavior of the customers wanting to buy the same product is called Repurchase Intention. Marketing Mix of 4Ps, consisting of Product, Price, Place, and Promotion is a product marketing tool crucial in determining customers’ Repurchase Intention. Moreover, Customer Satisfaction is believed to be a mediator between Marketing Mix of 4Ps and Repurchase Intention. Thus, Uniqlo is one brand which needs to enhance their marketing strategy since it is currently expanding in Indonesia. Therefore, this research is aimed to know the impact of Marketing Mix of 4Ps towards Repurchase Intention mediated by Customer Satisfaction.This research gathered data by spreading questionnaires to 176 people and simple random sampling method is being used to gather the data. The data are analyzed by multiple linear regression with path analysis and Sobel test. The findings show that Product and Price have influence towards Repurchase Intention. Furthermore, Customer Satisfaction mediates the relationship between Product and Price towards Repurchase Intention. Key WordsMarketing Mix, Customer Satisfaction, Repurchase Intention